Innovation of Indonesian Healthy Snacks Based on Purple Sweet Potatoes - Fathonah, Siti; Rosidah, Rosidah; Paramita, Octavianti; Karsinah, Karsinah (International Journal of Research Innovation and Entrepreneurship, 2020)
This study pointed out the innovation on Indonesian healthy snacks i.e. senteling and onde-onde made of purple sweet potatoes. The scope was focused on the quality assurance of those two snacks on two aspects of quality i.e. sensory quality and acceptability. This study used a purposive sampling technique. Different compositions of purple sweet potatoes were used for both snacks prepared in this study. In the case of sentiling, a composition of steamed purple sweet potatoes of 40-80 wt% (with a 20wt% increment) was used. In the case of onde-onde, a composition of purple sweet potatoes flour of 10-22 wt% (with a 6wt% increment) was used. The prepared snacks were examined through sequent sensory and acceptability tests involving eight panellists and 50 respondents, respectively. A single classification of variance analysis followed by Duncan test was used in the data analysis. The results revealed that sensory quality in senteling and onde-onde was almost the same, i.e. 5.5-7.4 and 5.3-7.2, respectively. The variations in acceptability of the two products differed greatly, 3.5-7.7 for senteling and 4.9-6.9 for onde-onde. The sensory quality was different for senteling in the overall aspect and elasticity, while in the case of onde-onde, it was different in the aspect of color, aroma, and flavor. The difference in acceptability in the case of senteling was observed in all aspects, whereas that difference was only observed in color and aroma aspects in the case of onde-onde. The best senteling in term of sensory quality and acceptability was obtained by the addition of 40 wt% of steamed purple sweet potatoes, while the best onde-onde was that with 16 wt% of purple sweet potatoes flour.